PENGEMBANGAN BAHAN AJAR E-BOOK EKOSISTEM SAWAH BERCIRIKAN ETNOSAINS BERBASIS MOBILE LEARNING KELAS V DI SD/MI - Puji Lestari; Sudi Dul Aji; Farida Nur Kumala (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rice field ecosystem is a crucial topic in elementary IPAS (Integrated Science and Social Studies) education, yet its presentation seldom relates to the local wisdom found in students’ surroundings. Therefore, the development of an ethnoscience-characterized rice field ecosystem e-book, delivered via mobile learning, is expected to enhance fifth graders’ contextual understanding of ecosystem concepts at UPT SD Negeri Resapombo 01. This development study aimed to evaluate the feasibility, practicality, and effectiveness of the e-book, which integrates ethnoscientific values and is accessible on mobile devices. This development research uses the ADDIE model with 5 stages, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. This research passed due diligence from media experts, material experts and language experts. The subject of this research involved teachers and fourth grade students, through two stages of limited field trials involving 10 students and a large field trial involving 20 students. Data was analyzed based on validation sheet instruments, questionnaires, and tests to assess the improvement in students’ understanding of the subject matter. The feasibility results showed that the media expert gave a score of 95.83%, the language expert 97.5%, and the material expert 90%, with an average feasibility score of 94.44%, categorized as "very feasible." The practicality level of the e-book as assessed by students in the limited field trial was 89.16%, and 90.41% in the broader field trial, both falling into the "very practical" category. The practicality assessment by teachers yielded a score of 94.73%, also categorized as "very practical." The effectiveness test produced an N-Gain score of 0.67, which falls into the "moderate" category. It is concluded that the ethnoscience-based e-book is feasible, practical, and effective to be used as teaching material that integrates local wisdom in elementary schools.